Norbert Dannhaeuser, Contemporary Trade Strategies in the Philippines: a Study in Marketing Anthropology, New Brunswick, Rutgers University Press, 1983. - Beckett, Jeremy (Estudios de Asia y África, 1988)
Traducción del inglés: Mariela Álvarez